Survey on trusted cloud platform technology - Xinfeng HE; Junfeng TIAN; Fanming LIU (Tongxin xuebao)
Information security technology confronts severe challenges because of the safety demands of cloud computing.The trustworthiness and self-safety of cloud computing platform are the foundation of cloud computing security.The confidence of cloud users is the key issue the deep development and popularization for cloud computing.The trusted cloud computing technology provides a feasible solution.From the standpoint of guaranteeing the trustworthiness of cloud computing platform,related research progresses on trusted virtualization,construction of trusted cloud platform and trusted virtual machine were introduced.Additionally,the characteristics,application scopes and effectiveness of typical schemes were analyzed and compared.Finally,current limitations and possible directions for future research were discussed.